COMPORTAMENTO DA TURBIDEZ E MATERIAL EM SUSPENSÃO, EM UM RIO COM VAZÃO REGULARIZADA POR SISTEMA DE BARRAGENS EM CASCATA: RIO SÃO FRANCISCO (NE, BRASIL) - Medeiros, Paulo Petter; Segundo, Geórgenes Hilário Cavalcante; Magalhães, Enaide Marinho Melo (Geochimica Brasiliensis, 2015)
Turbidity and suspended matters are important parameters utilizedin the water quality monitoring at the surface–water interface. The SãoFrancisco River (NE-Brazil) is considered a medium to large-size river ofeconomic, ecological and social importance. The objective of this work wasto evaluate the influence of river discharge and precipitation on turbidityand suspended matter concentration. The fieldwork was carried out in thelower sector of the São Francisco River on a monthly scale within 2001,2004 and 2007. The Van Dorn bottle was utilized to collect the samplesat the sub-surface level with suspended matter analyzed at the laboratory,while turbidity was measured in situ. The year 2001 showed the lowestconcentrations of suspended matters and turbidity with average of 4.8±2.1 mg/Land 2.7±2.0 NTU, respectively. Suspended matters and turbidity indicate thatthe year 2004 had the highest annual mean values with 72.0±148.9 mg/L and101.0±146.0 NTU, respectively. The results reveal that the geographical locationof the precipitation in the São Francisco River basin plays a major role in increasingthe suspended matters and turbidity concentrations in the lower sectorof the river, being more important than the total precipitation rate. The lack ofcorrelation between suspended matters and turbidity with river discharge revealedthe influence of the water discharge management aiming to maximize thehydropower electricity generation.